Using SPSS syntax a beginner's guide - Collier, Jacqueline (Los Angeles, [Calif.] ; London : SAGE, 2009)
SPSS syntax is the command language used by SPSS to carry out all of its commands and functions. In this book, Jacqueline Collier introduces the use of syntax to those who have not used it before, or who are taking their first steps in using syntax.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; SPSS (Computer file); Social sciences -- Statistical methods